1996
DOI: 10.2105/ajph.86.1.93
|View full text |Cite
|
Sign up to set email alerts
|

Why are most drowning victims men? Sex differences in aquatic skills and behaviors.

Abstract: Men have higher drowning rates than women for most age groups. Data from a 1991 national household survey (n = 3042) on aquatic activities were used to examine hypotheses about differential drowning rates by sex. Men and women were compared by (1) exposure to aquatic environments; (2) frequency of aquatic activities involving or potentially involving, submersion; (3) swimming training and ability; (4) aquatic risk-taking behaviors; and (5) alcohol use on or near the water. Men had elevated risks for exposure, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
114
1
5

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(135 citation statements)
references
References 3 publications
15
114
1
5
Order By: Relevance
“…A 1988-1992 study, which used similar case definitions, found a rate of 20 per 100,000 (1). Drowning fatality rates were found to be much higher for males than for females, likely explained by earlier findings that males have a higher exposure to water environments and engage in riskier behaviours on the water (18).…”
Section: Determinationsmentioning
confidence: 82%
See 2 more Smart Citations
“…A 1988-1992 study, which used similar case definitions, found a rate of 20 per 100,000 (1). Drowning fatality rates were found to be much higher for males than for females, likely explained by earlier findings that males have a higher exposure to water environments and engage in riskier behaviours on the water (18).…”
Section: Determinationsmentioning
confidence: 82%
“…Each of these can lead to submersion and death by drowning. However, if the victim is wearing a flotation device and does not become completely submerged, he/she may survive up to six hours before hypothermia is severe enough to become life-threatening (18). Data on water temperature and duration of immersion that would allow discrimination between cold shock, swimming failure and hypothermia are not routinely recorded (20), but such data might be pivotal in convincing marine travellers to wear flotation devices or survival gear.…”
Section: Use Of Personal Flotation Devices (Pfd)mentioning
confidence: 99%
See 1 more Smart Citation
“…Drowning is the second-leading cause of injury-related death among children under the age of 15 years (Centers for Disease Control and Prevention). A survey of aquatic skills and behaviors found that men not only have greater exposure to aquatic settings but also spend more time in higher risk aquatic activities during which submersion incidents might occur (Howland, Hingson, Mangione, Bell, & Bak, 1996), resulting in a drowning rate for men four times higher than that for women (Gilchrist, 2000).…”
Section: Rate Of Aquatic Incidentsmentioning
confidence: 99%
“…We defined icy water as a water temperature below 10°C, as this is a life threatening temperature [14]. As the mean water temperature in the local river is below 10°C between December-April, we chose to define drowning in the open water in this time period as icy [15].…”
Section: Introductionmentioning
confidence: 99%